2021
DOI: 10.7759/cureus.18420
|View full text |Cite
|
Sign up to set email alerts
|

Large Lipoma of the Mouth Floor

Abstract: Lipomas are one of the most common benign connective tissue masses in the human body. They rarely cause issues and are typically removed for cosmetic reasons. They rarely appear in the oral cavity though they are common. Thus, only a few sublingual lipoma cases have been reported. We present a case of a male in his 60s who came to our clinic complaining of dysphagia and dysarthria caused by an oral swelling from a right sublingual simple lipoma. It was decided to be removed surgically under general anesthesia,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…K. Gibson et al described another similar clinical case; they reported a case of a large lipoma of the mouth floor (8.5 × 4.0 × 1.0 cm), excised with neuromonitoring of the right hypoglossal nerve, with a definitive histological diagnosis of simple lipoma without invasion of the surrounding tissues; no focal cartilage metaplasia was described 4 …”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…K. Gibson et al described another similar clinical case; they reported a case of a large lipoma of the mouth floor (8.5 × 4.0 × 1.0 cm), excised with neuromonitoring of the right hypoglossal nerve, with a definitive histological diagnosis of simple lipoma without invasion of the surrounding tissues; no focal cartilage metaplasia was described 4 …”
Section: Discussionmentioning
confidence: 96%
“…10 K. Gibson et al described another similar clinical case; they reported a case of a large lipoma of the mouth floor (8.5 × 4.0 × 1.0 cm), excised with neuromonitoring of the right hypoglossal nerve, with a definitive histological diagnosis of simple lipoma without invasion of the surrounding tissues; no focal cartilage metaplasia was described. 4 Differential diagnoses are very important and physician should base their considerations on patients' history and physical examination, imaging, and pathological findings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations